Elementary School Students Intention to Use Google Classroom Application: Extended TAM Model - Mardhiyah Widya Ningsih; Zulherman Zulherman (AL-ISHLAH: Jurnal Pendidikan, 2022)
Online learning during the pandemic has required teachers and students to utilize the existing technology. This research aims to determine students' perceptions of Google Classroom usage during the COVID-19 pandemic based on the TAM model by adding an external variable, e.g., motivation. Google Classroom can make online learning much easier to be used. Additionally, Google Classroom helps motivate pupils to learn online. However, it has not been any detailed research that investigated the use of Google Classroom in Elementary School based on the TAM Model. This quantitative study uses a survey design and technology acceptance model approach to measure students' interest in using the Google Classroom application. The data was collected through a questionnaire for grade IV students, as many as 90 students. The research findings were analyzed using Partial Least Square Structural Modeling (PLS-SEM) approach in the testing model, and the hypothesis testing reveals that generally, students like Google Classroom during COVID-19. Most elementary school students agree that Google Classroom is easy to use and effective in learning. Students were driven to use Google Classroom throughout the pandemic. Google Classroom helps them absorb lessons. Using Google Classroom can enhance students' motivation to study during the Google Classroom epidemic.